2020
DOI: 10.1002/anie.201914596
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Conversion of Propargylic Amines and CO2 Catalyzed by Noble‐Metal‐Free [Zn116] Nanocages

Abstract: The reaction of propargylic amines and CO 2 can provideh igh-value-added chemical products.H owever,m ost of catalysts in such reactions employn oble metals to obtain high yield, and it is important to seek eco-friendly noble-metalfree MOFs catalysts.H ere,agiant and lantern-like [Zn 116 ] nanocage in zinc-tetrazole 3D framework [Zn 22 (Trz) 8 (OH) 12 -(H 2 O) 9 ·8 H 2 O] n Trz = (C 4 N 12 O) 4À (1)w as obtained and structurally characterized.I tc onsists of six [Zn 14 O 21 ]c lusters and eight [Zn 4 O 4 ]c lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 91 publications
2
52
0
1
Order By: Relevance
“…However, catalytic sites in the micro‐structure remain unchanged and do not fall out from the framework, thus concluding the post‐catalysis structure is stable. The similar PXRD change has been already observed for many other recyclable MOF‐based catalysts [15, 24] . For comparison, the catalytic activity of a serious of inorganic silver salts for this model reaction has also been studied.…”
Section: Resultssupporting
confidence: 72%
“…However, catalytic sites in the micro‐structure remain unchanged and do not fall out from the framework, thus concluding the post‐catalysis structure is stable. The similar PXRD change has been already observed for many other recyclable MOF‐based catalysts [15, 24] . For comparison, the catalytic activity of a serious of inorganic silver salts for this model reaction has also been studied.…”
Section: Resultssupporting
confidence: 72%
“…The formation of carbamato complexes is considered a key step in metal-mediated reactions such as the CO 2 /aziridine coupling [306][307][308] and the CO 2 cycloaddition to propargyl amines [113,[309][310][311][312] or aminoalcohols [306]. The production of oxazolidinones (cyclic carbamates) via CO 2 /aziridine coupling is one of the most widely investigated carbon dioxide fixation processes, and many species have been evaluated as catalytic precursors, such as Al(III) [313], Cr(III) [314] and Co(III) [315] salen complexes, and Cu(II) [316] and Zn(II) [317] porphyrin complexes.…”
Section: Co 2 Activation Routesmentioning
confidence: 99%
“…However, catalytic sites in the micro-structure remain unchanged and do not fall out from the framework, thus concluding the postcatalysis structure is stable.T he similar PXRD change has been already observed for many other recyclable MOF-based catalysts. [15,24] Forc omparison, the catalytic activity of as erious of inorganic silver salts for this model reaction has also been studied. Control experiments indicated that the homogenous AgStBu and CF 3 COOAg provided low yields under similar conditions (Table 1, entries 8and 9).…”
Section: Resultsmentioning
confidence: 99%